2011
DOI: 10.3892/mmr.2011.672
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference-mediated silencing of SOCS-1 via lentiviral vector promotes apoptosis of alveolar epithelial cells in vitro

Abstract: Abstract. Suppressor of cytokine signaling-1 (SOCS1) is a protein that negatively regulates cytokine and growth factor signaling. However, little is known regarding the precise role it plays in idiopathic pulmonary fibrosis. The aim of the present study was to construct a recombinant lentiviral vector for RNA interference targeting the SOCS1 gene and to detect the expression in human alveolar epithelial cells. A lentiviral vector-mediated RNA interference method was used to establish a SOCS1-negative cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This suggests that endogenous SOCS1 expression was essential for and tightly regulated in TE671 cells. Indeed, it was reported that lentiviral vector-mediated SOCS1 shRNA transduction promoted apoptosis of alveolar epithelial cells [44] . It is also plausible that the siRNA was sensed by intrinsic immunity followed by up-regulation of SOCS1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that endogenous SOCS1 expression was essential for and tightly regulated in TE671 cells. Indeed, it was reported that lentiviral vector-mediated SOCS1 shRNA transduction promoted apoptosis of alveolar epithelial cells [44] . It is also plausible that the siRNA was sensed by intrinsic immunity followed by up-regulation of SOCS1 expression.…”
Section: Discussionmentioning
confidence: 99%